COVID-19 and external shock : economic impacts and policy options - Jaramillo, Miguel (2020)
Latin America is currently suffering from two independent but related shocks: the impact of COVID-19 and the shock of commodity prices. Peru, we argue, is a case in which the strongest impact comes from the pandemic. Peru was the first country in Latin America to react and implement sanitary and economic measures against the coronavirus. The country has been in mandatory quarantine since Monday, March 16. This carries very important challenges for all economic actors. Global and national activity has suffered a sudden stop with direct implications for: (i) the income generating capacity of independent workers, (ii) the jobs of formal and informal and informal workers, and (iii) the survival of small, medium and large companies. In this note we consider the situation of Peruvian households in the face of the pandemic, exploring their vulnerabilities through an analysis of their main source of income generation: work. We also consider the situation of the companies that employ the workers under analysis. We present an overview of what the government’s main action have been so far and offer some recommendations.